Power relations and fool-master discourse in Shakespeare: a discourse stylistics approach to dramatic dialogue - Calvo, Clara (1990)
This study undertakes an examination of fool-master discourse in Shakespeare with the help of discourse stylistics, an approach to the study of literary texts which combines findings from the fields of discourse analysis, conversation analysis and pragmatics. The analysis aims to show how the relations of power which exist between dramatic characters are manifested by the linguistic organization of the dialogue as interactive process.